A Global View of Neonatal Asphyxia and Resuscitation - Moshiro, Robert; Mdoe, Paschal; Perlman, Jeffrey M. (Frontiers in Pediatrics, 2019)
Birth asphyxia (BA), assumed to be related to intrapartum related hypoxia- ischemia, accounts for one million neonatal deaths annually. In the low resource setting BA is usually defined as a failure to initiate or sustain spontaneous breathing at birth. In the resource replete setting BA is a biochemical definition related to impaired gas exchange, due to interruption of placental blood flow (PBF). An umbilical arterial pH <7.00 referred to as severe fetal acidemia, reflects a degree of acidosis, where potential risk of adverse neurologic sequelae is increased. However even with this degree of acidemia, the likelihood of mortality or adverse neurologic sequelae remains low. With asphyxia, the fetus aims to redistribute cardiac output to protect more vital organs e.g., brain, myocardium, and adrenal gland at the expense of decreased flow to organs such as kidney or intestine. Furthermore in an experimental model, newborns subjected to asphyxia immediately develop primary apnea with bradycardia compensated blood pressure and normal pH, with recovery of respirations following basic interventions i.e. stimulation coupled with reversal of the asphyxial state. However if asphyxia is sustained, secondary apnea manifests with bradycardia, hypotension and pH <7.00. More intensive resuscitation including bag mask ventilation ± intubation ± cardio-pulmonary resuscitation maybe necessary for correction upon reversal of asphyxia. Identification of a severely acidemic state (cord arterial pH < 7.00) in the newborn, may help to differentiate the truly asphyxiated intrapartum related cases that result in mortality, from those cases where mortality is related to delay in or ineffective basic resuscitation.